Hexagonal RMnO3: a model system for two‐dimensional triangular lattice antiferromagnets. Issue 1 (1st February 2016) - Sim, Hasung; Oh, Joosung; Jeong, Jaehong; Le, Manh Duc; Park, Je-Geun
Abstract : Here we present a review of the crystal and magnetic structure as well as the spin dynamics of two‐dimensional triangular lattice multiferroic hexagonal manganite R MnO3 . Abstract : The hexagonal R MnO3 ( h ‐ R MnO3 ) are multiferroic materials, which exhibit the coexistence of a magnetic order and ferroelectricity. Their distinction is in their geometry that both results in an unusual mechanism to break inversion symmetry and also produces a two‐dimensional triangular lattice of Mn spins, which is subject to geometrical magnetic frustration due to the antiferromagnetic interactions between nearest‐neighbor Mn ions. This unique combination makes the h ‐ R MnO3 a model system to test ideas of spin‐lattice coupling, particularly when both the improper ferroelectricity and the Mn trimerization that appears to determine the symmetry of the magnetic structure arise from the same structure distortion. In this review we demonstrate how the use of both neutron and X‐ray diffraction and inelastic neutron scattering techniques have been essential to paint this comprehensive and coherent picture of h ‐ R MnO3 .